2014
DOI: 10.1080/1573062x.2014.900091
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stratigraphy and slope on the drainage capacity of permeable pavements: laboratory results

Abstract: A small size laboratory test-bed has been realized at the University of Genoa in order to evaluate the drainage capacity of permeable pavements by monitoring inflow, runoff and subsurface outflow. The laboratory test programme has been designed in order to investigate the influence of the rainfall intensity and pavement slope on the hydrologic response of permeable pavements. Four permeable pavement systems realized combining two paver typologies (concrete cell and pervious brick) with two filter layers made o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…The tests were performed in a small size laboratory test-bed realized at the University of Genoa to investigate the hydrologic response of an infiltration system per unit surface area under varying slope and rainfall conditions. The test-bed is composed of a plot (1 Â 2.5 m), a rainfall simulator system, three cylindrical reservoirs and an automated monitoring system for measuring inflow and outflow; the detailed description of the laboratory device is provided elsewhere (Palla et al, 2015). The tested green roof solutions can be classified as extensive green roofs (Berretta et al, 2014); in detail the stratigraphy is primarily comprised of a growing medium (total depth of 12 cm) and a loose-laid synthetic specialized layer (drainage and filter layers for a total depth of 2.5 cm).…”
Section: The Lid Control Modulesmentioning
confidence: 99%
“…The tests were performed in a small size laboratory test-bed realized at the University of Genoa to investigate the hydrologic response of an infiltration system per unit surface area under varying slope and rainfall conditions. The test-bed is composed of a plot (1 Â 2.5 m), a rainfall simulator system, three cylindrical reservoirs and an automated monitoring system for measuring inflow and outflow; the detailed description of the laboratory device is provided elsewhere (Palla et al, 2015). The tested green roof solutions can be classified as extensive green roofs (Berretta et al, 2014); in detail the stratigraphy is primarily comprised of a growing medium (total depth of 12 cm) and a loose-laid synthetic specialized layer (drainage and filter layers for a total depth of 2.5 cm).…”
Section: The Lid Control Modulesmentioning
confidence: 99%
“…Results showed that there was no runoff observed from both permeable pavements in the first 15 min of constant rainfall intensity. In addition, the study indicated that the higher slope and bigger aggregate size enhanced the drainage [17]. Similarly, Drake [18] investigated permeable pavement performance and showed it can reduce runoff volumes by up to 43% in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have indicated that rainfall runoff from permeable pavement is notably less as compared to traditional pavement (asphalt pavement) [13,16,17]. Collins et al [16] investigated the hydrological performance of four different permeable pavements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies have shown that permeable pavements have many potential benefits such as the reduction of runoff volumes [4][5][6][7][8], limitation of peak flows [2,9,10], recharge of groundwater [7,11], and prevention of water pollution [6,12,13], because the infiltration of water through the pavement layers traps pollutants [10,14]. In addition, many permeable pavements have a high albedo (light reflectivity) [15], reduced runoff temperature [16], and improved aesthetics.…”
Section: Introductionmentioning
confidence: 99%